Preliminary evidence for the acceptability, safety, and efficacy of the flash technique - Manfield, Philip E.; Taylor, Graham; Dornbush, Edie; Engel, Lewis; Greenwald, Ricky (Frontiers in Psychiatry, 2024)
Objectives: This paper reports on four similar studies intended to explore the acceptability, safety, and efficacy of The Flash Technique (FT), a method of rapidly reducing the intensity of a disturbing memory or image, with minimal subjective disturbance for subjects during the process. Of the four studies, two were conducted during FT trainings in the United States, one in Australia, and one in Uganda.The studies involve pre-post-and follow-up repeated measures to determine the effectiveness of a fifteen minute FT intervention. A total of 654 subjects who were asked to think of a disturbing memory, and then participate in a structured experience of FT. The purpose of this investigation was to determine if a brief application of FT would be safe and effective in significantly reducing their disturbance, In each study, subjectssubjects rated their disturbing memories on a 0 to 10 scale with zero representing no disturbance at all and 10 representing the worst they could imagine. Then they took part in a 15-minute group practicum where they were guided in self-administering FT with no individual supervision or support.In all four studies, the mean reduction in disturbance exceeded two thirds, the results were significant (p<.001), and the effect size was very large. Of the 813 sessions (654 subjects) represented in these studies, only two subjects reported slight increases in disturbances, and both of these subjects reported reductions in disturbance in their second FT experiences two hours later. At four-week follow-up, mean disturbance levels in all four studies indicated maintenance of benefit or slight further reduction of mean disturbance levels. An 18-month follow-up with a sub-group of subjects who initially reported a high level of memory-related distress found similar maintenance of gains as well as symptom reduction.Conclusion: These findings provide preliminary evidence of FT's acceptability, safety, and efficacy. Further study is warranted.